Mock-epic poetry from Pope to Heine - Robertson, Ritchie (Oxford : Oxford University Press, 2009)
This is a study of 18th- and early 19th-century poetry in English, French and German, focusing on the mock epic (from Pope's 'Dunciad' to Byron's 'Don Juan') as a critique of serious epic poetry and also as a literary means of exploring a wide range of sexual and religious issues in a humourous style.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Mock-heroic literature -- History and criticism; English poetry -- 18th century -- History and criticism; French poetry -- 18th century -- History and criticism; German poetry -- 18th century -- History and criticism; English poetry -- 19th century -- History and criticism; French poetry -- 19th century -- History and criticism; German poetry -- 19th century -- History and criticism